Emmons, Washington County - Green, Edward (Kansas State University, The Chapman Center for Rural Studies, 2012)
The author uses historic documents and many oral interviews to recall the past of the once thriving town of Emmons, KS
Edward Green, “Emmons, Washington County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/76.
Keywords: B&M Railroad; Emmons; Emmons Community Club; Pacific Railroad Act; School District no. 2; George W. Roberts